Circumpolar Health Atlas - Rawat, Rajiv; Young, T. Kue (Book collections on Project MUSE., 2015)
"The Circumpolar Health Atlas is also an informative and practical reference guide for health researchers, service providers, and policy makers, as it offers a broad, multidisciplinary understanding of the health of diverse populations who inhabit the polar regions of the northern hemisphere. The atlas includes overviews of the physical environment that influences human health; cultures and languages of northern peoples; different diseases and health conditions; and health systems, policies, resources, and services. It concludes with information on how education and research can be used to improve health in these regions."--Pub. desc.